De-industrialization, re-industrialization, and the resurgence of state capitalism: The case of Indonesia - Kyunghoon Kim; Andrew Sumner (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2019)
Discussions on the developing world's industrial policies have largely neglected the role of state-owned entities. This paper argues that the resurgence of state capitalism has been, in part, the response of developing countries to the recent pattern of structural transformation involving weak manufacturing. Using the case of Indonesia, this paper demonstrates that many middle-income countries have large and diverse state-owned entities in their development policy toolbox and have begun to experiment with these tools in order to change the pace and characteristics of structural transformation. Considering these trends, there is a need to reconsider or 'normalize' the debate on the positive role that state-owned entities can play in stimulating structural transformation and on the institutional and policy design that can foster that role.
Keywords: G20; H70; L52; O14; 330; Indonesia; industrialization; industrial policy; infrastructure; state-owned enterprises